The effect of aging on infliximab exposure and response in patients with inflammatory bowel diseases. Issue 10 (27th March 2021) - Kantasiripitak, Wannee; Verstockt, Bram; Alsoud, Dahham; Lobatón, Triana; Thomas, Debby; Gils, Ann; Vermeire, Séverine; Ferrante, Marc; Dreesen, Erwin
Abstract : Aims: Controversies regarding infliximab treatment in elderly patients with inflammatory bowel diseases remain. We evaluated the effect of patient's age on infliximab exposure, efficacy and safety. Methods: Retrospective case‐control data of patients receiving infliximab induction treatment were analysed. A population pharmacokinetic model was developed to estimate individual pharmacokinetic parameters. A logistic regression model was used to investigate the effect of exposure on endoscopic remission. Repeated time‐to‐event models were developed to describe the hazard of safety events over time. Results: A total of 104 patients (46 elderly, ≥65 years) were included. A two‐compartment population pharmacokinetic model with linear elimination adequately described the data. Infliximab clearance decreased with older age, higher serum albumin, lower fat‐free mass, lower C‐reactive protein and absence of immunogenicity. Yet, infliximab exposure was not significantly different between elderly and nonelderly. Regardless of age, an infliximab trough concentration at week (w)14 of 15.6 mg/L was associated with a 50% probability of attaining endoscopic remission between w6 and w22. Infliximab exposure during induction treatment was not a risk factor of (severe) adverse events. The hazard of severe adverse events and malignancy increased by 2% and 7%, respectively, with increasing year of age. Concomitant immunomodulator use increased the hazard of infection by 958%, regardless of age. Conclusions: Elderly patients attained infliximab exposure and endoscopic remission similarly to nonelderly patients. Therefore, the same infliximab trough concentration target can be used in therapeutic drug monitoring. The hazards of severe adverse events and malignancy increased with age, but not with infliximab exposure.